Desenvolvimento de um inclinômetro com tecnologia mems aplicado ao monitoramento de obras geotécnicas - Penz, Rodrigo Siqueira (2014)
The inclinometer is a device that makes the measurements of angulations regarding the gravitational vertical along the amount column of a slope, in order to check the existence of transversal movements, comparing values of measurements in different periods. This work performs studies and developments which contribute to the evolution of the inclinometers used in geotechnical tasks, and in this work it is denominated SADi (Inclination Data Acquisition System). SADi initially presents in its probe an electric circuit of inclination measurements based on MEMS technology (Microelectromechanical System), which makes instant measurements in two orthogonal directions in relation to each other and in relation to the probe body. Yet, the probe presents a decrease in the distance among its guide casters, providing this way a higher number of measurement intervals, without losing the characteristic of operating in the standard guide tube. SADi also presents the innovation in the measurement of the depth of the probe, in an automatic and synchronized way with the inclination measurements of the two directions of the axis. As user interface SADi uses a personal computer (PC), notebook, tablet or windows phone, which helped by a program makes the indication of the instant inclination on its screen, as well as the storage of the measurements data in the CSV file. In SADi the mailing of data which come from the probe and from the depth measurement system to the PC happens through wireless communication. The results, testing, calibration and validation of SADi are presented in this paper